Analisis Putusan Pengadilan Agama Kediri Nomor 0026/PDT.G/2020/PA.KDR Tentang Cerai Gugat - Siti Lailatul Rif'ah al Fariza; Kafi Muhammad Fahruddin; Mohammad Farid; Nur Laili Kasanah; Nur Aini; Siti Khotimatun Khasanah; Sanuri . (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
Abstract: This study aims to analyze the Decision of the Religious Court of the City of Kediri Number 0026/Pdt.G/2020/PA.Kdr regarding litigation. This research is juridical-normative research based on the results of data analysis of literature studies to obtain primary and secondary data. The data are collected into one; then, the data is analyzed using inductive analysis. In this case, the consideration of the judges of the Religious Court of Kediri City referred to Article 22 of Government Regulation Number 9 of 1975 and Article 116 letter (f) Compilation of Islamic Law as well as evidence and witnesses from the plaintiffs that were proven to be true. In Islamic law, it has been explained that